The Art of Solitude from Modernism to Postmodernism and Beyond - Stern, Julian (Ruch Filozoficzny, 2024)
A philosophical anthropology of solitude is presented through the art, literature and music of and around Modernism, Postmodernism. It is presented as an insight into both Modernism and Postmodernism. These movements portrayed and contributed to the lonely alienated worlds of the early-to-mid twentieth century. Culture and society together developed forms of loneliness that were centred on individualist, alienated, guilt and shame, to which a response may be appropriately silent or humorous, living or dead, and sometimes a lewd masochism. Even those who rejected Modernism and Postmodernism help describe – either positively or apophatically – the distinctive forms of lonely solitude in those movements.